Calculation of Active Earth Pressure in Cohesive Soils Based on Slope Stability - Shi-Wei Wu; Tao Yang; De-Pei Zhou; Han-Qing Teng; Zhe Zhang (Salehan Institute of Higher Education, 2026)
Extensive engineering experience has shown that the stability of cohesive soil slopes behind retaining walls has a significant impact on earth pressure. This manuscript investigates the influence of the stability of a cohesive soil slope behind a retaining wall on earth pressure. To elucidate the patterns of how slope stability affects earth pressure, first, an analysis of the interaction mechanism between the wall and the slope was carried out to clarify the mechanical behavior of clay soil pressure. Secondly, based on the assumption of plane slip damage and limit equilibrium condition, the active earth pressure calculation equation for cohesive soil considering slope stability was proposed. Thirdly, based on the proposed equation, this manuscript analyzed the influence of various slope parameters on earth pressure and proposed a method for determining the most dangerous slip surface and inclination angle of a slope. Finally, the validity of this equation was verified through a large number of arithmetic examples. These results can be conveniently and easily applied to the calculation of earth pressures in slopes with clayey and sandy soil and also provide a new approach and reference for gaining a deeper understanding of the complex mechanical behavior of earth pressure in cohesive soils.